Integrasi Idealisme dan Realisme dalam Pengambilan Keputusan Manajerial Sekolah Dasar: Kajian Literatur dengan Perspektif Aksiologi - Al-Fitrie, Ahmad Lazuardi; Jaenudin, Dadang (Lembaga Sosial Rumah Indonesia, 2026)
Purpose – This study aims to examine the integration of idealism and realism in managerial decision-making at the elementary school level through the perspective of educational axiology.Methods – The study employs a Systematic Literature Review (SLR) of articles indexed in Scopus, SINTA, and DOAJ published between 2021 and 2025. Literature selection followed inclusion–exclusion criteria and the PRISMA procedure, resulting in 25 eligible articles, which were analyzed using thematic synthesis.Findings – The results indicate that idealism functions as a moral–philosophical foundation in shaping educational decisions, whereas realism provides empirical grounding that ensures decisions are contextually feasible and implementable. Axiology emerges as the integrative bridge connecting ethical values to practical execution, producing a conceptual managerial model based on value balance. The review also identifies several determining factors for successful integration, including leadership orientation, school culture, resource capacity, and institutional value documentation. Research Implications – Theoretically, this study contributes a synthesized model of axiological integration between idealism and realism, offering a conceptual foundation for future value-based educational management research. Practically, it provides direction for school leaders and policymakers to develop decisions that are ethically anchored yet operationally adaptive. The study is limited to a literature-based review without empirical field validation; therefore, future research is recommended to test the model through case studies, field surveys, or measurement instrument development.